Proceedings of IEEE. IEEE Region 10 Conference. TENCON 99. 'Multimedia Technology for Asia-Pacific Information Infrastructure'
DOI: 10.1109/tencon.1999.818625
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of wet gate oxide device and nitride oxide (NO) device

Abstract: In this paper we fabricated and tested the 0 . 2 6 P NMOSFET with wet gate oxide and nitride oxide gate to compare that the characteristics of hot carrier effect, charge to breakdown, transistor Id-Vg curve, charge trapping, and SILC(Stress Induced Leakage Current) using the HP4145 device tester As a result we find that the characteristics of nitride oxide gate device better than wet gate oxide device, especially hot carrier lifetime (nitride oxide .gate device satisfied 30years, but the lifetime of wet gate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…(1) The CV curves (a) and (b) corresponding respectively to the 'wet N 2 0 oxide' grown at 800°C and the oxide grown in dry oxygen annealed in N 2 0 at 800°C show the expected high frequency characteristics with the well defined accumulation, depletion and inversion region with' a shift slightly more towards the negative axis compared to others indicating higher value of fixed oxide charge in this case. This is attributed to the introduction of significant amount of nitrogen in the tunnel oxide as reported in the literature [14]. (2) The CV curve (c) corresponding to the device having 'wet N 2 0 oxide' grown at 760°C shows similar well defined high frequency CV characteristics, but with a comparatively less negative value of the flat band voltage indicating that the nitrogen incorporation is less due to the lower oxidation temperature.…”
Section: Part-1: Studies Of Wet N 2 0 Oxide With Ai Gate Mos Capacitomentioning
confidence: 61%
See 1 more Smart Citation
“…(1) The CV curves (a) and (b) corresponding respectively to the 'wet N 2 0 oxide' grown at 800°C and the oxide grown in dry oxygen annealed in N 2 0 at 800°C show the expected high frequency characteristics with the well defined accumulation, depletion and inversion region with' a shift slightly more towards the negative axis compared to others indicating higher value of fixed oxide charge in this case. This is attributed to the introduction of significant amount of nitrogen in the tunnel oxide as reported in the literature [14]. (2) The CV curve (c) corresponding to the device having 'wet N 2 0 oxide' grown at 760°C shows similar well defined high frequency CV characteristics, but with a comparatively less negative value of the flat band voltage indicating that the nitrogen incorporation is less due to the lower oxidation temperature.…”
Section: Part-1: Studies Of Wet N 2 0 Oxide With Ai Gate Mos Capacitomentioning
confidence: 61%
“…As the oxide 1ickness control was difficult in a high temperature rocess due to the high growth rate, it was necessary to arry out low temperature thermal oxidation in pure N 2 0. lowever, it has been shown that the low temperature titridation in N 2 0 does not introduce any significant titrogen [11]. Recently, it has been reported that 1itridation of wet or dry oxides in nitric oxide [12][13][14][15] Jrovides good immunity to trap build-up, good interface md high charge to breakdown (Qhd).lt has also been noted :hat heavy nitridation introduces traps at the interface and ts found to be responsible for degradation of the device performance under high current operations [ 16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the low temperature nitridation in N 2 O does not introduce any significant nitrogen [7]. During the past decade, it has been reported that nitridation of wet or dry oxides in nitric oxide [14,15,16,17] provides reasonably good immunity to trap build-up, fairly good interface and high charge to breakdown (Q bd ). It has also been reported that heavy nitridation introduces traps at the interface and is found to be responsible for degradation of the device performance under high current operations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various approaches, nitridation of the thermal oxide of silicon using nitrous oxide (N 2 O) or nitric oxide (NO) has shown great promise as a reliable dielectric capable of resistance against radiation and high-field stress damage [1]- [4]. Recent studies [5], [6] have shown that N 2 O or NO annealing of wet thermal oxide results in tunnel oxides with low trap density and low values of stress-induced leakage current characteristics. A recent study [7] has shown that heavy nitridation degrades the breakdown property of the periphery gate oxide.…”
Section: Introductionmentioning
confidence: 99%